Warming, but Not Acidification, Restructures Epibacterial Communities of the Baltic Macroalga Fucus vesiculosus With Seasonal Variability - Mensch, Birte; Neulinger, Sven C.; Künzel, Sven; Wahl, Martin; Schmitz, Ruth A. (Frontiers in Microbiology, 2020)
Due to ocean acidification and global warming, surface seawater of the western Baltic Sea is expected to reach an average of ∼1100 μatm pCO2 and an increase of ∼5°C by the year 2100. In four consecutive experiments (spanning 10–11 weeks each) in all seasons within 1 year, the abiotic factors temperature (+5°C above in situ) and pCO2 (adjusted to ∼1100 μatm) were tested for their single and combined effects on epibacterial communities of the brown macroalga Fucus vesiculosus and on bacteria present in the surrounding seawater. The experiments were set up in three biological replicates using the Kiel Outdoor Benthocosm facility (Kiel, Germany). Phylogenetic analyses of the respective microbiota were performed by bacterial 16S (V1-V2) rDNA Illumina MiSeq amplicon sequencing after 0, 4, 8, and 10/11 weeks per season. The results demonstrate (I) that the bacterial community composition varied in time and (II) that relationships between operational taxonomic units (OTUs) within an OTU association network were mainly governed by the habitat. (III) Neither single pCO2 nor pCO2:Temperature interaction effects were statistically significant. However, significant impact of ocean warming was detected varying among seasons. (IV) An indicator OTU (iOTU) analysis identified several iOTUs that were strongly influenced by temperature in spring, summer, and winter. In the warming treatments of these three seasons, we observed decreasing numbers of bacteria that are commonly associated with a healthy marine microbial community and—particularly during spring and summer—an increase in potentially pathogenic and bacteria related to intensified microfouling. This might lead to severe consequences for the F. vesiculosus holobiont finally affecting the marine ecosystem.